To 'all the monster girls': violence and non-normativity in Noelle Stevenson's Nimona. Issue 6 (2nd November 2017) - Precup, Mihaela
ABSTRACT: Situated in a world that incorporates well-known tropes from medieval romances, as well as fantasy and science fiction elements, Noelle Stevenson's Nimona (2015) attempts to establish 'monster' as an ambiguous non-normative category and a pretext for interrogating common definitions of what makes one human. In this article, I am interested in examining the manner in which the ambiguous nature of the title character – a combination of human-animal, vulnerable-immortal, girl-monster – helps unveil the questionable nature of pre-established definitions of good and evil, as well as the connection between violence and the construction of social roles such as 'hero' and 'monster'. I also argue that the comic productively positions monstrosity at the intersection of violence, cuteness and queerness, and thus manages to unveil not only the subversive potential of a specific kind of cuteness, but also a usable alternative to the aesthetics of the heroic body.